Sistem Pendukung Keputusan Kelayakan Penerima Bantuan Dana KIP Kuliah Menggunakan Metode ROC-EDAS - Agus Iskandar (Building of Informatics, Technology and Science (BITS), 2022)
Education is one of the keys in achieving the ideals of the nation's children, there are often economic or financial constraints for the Indonesian people who are unable to be able to attend higher education stages, this makes the ideals of the nation's generation to be smart and have the potential to build the nation. being more advanced becomes hampered, this phenomenon makes the government take action in making an assistance program in the form of a card called the smart Indonesia card or (KIP), the provision of scholarship funds in the smart Indonesia card program of course has terms and conditions that can be met to get the right and disbursement of funds, the number of students who want to get KIP (Smart Indonesia Cards) aid funds makes the manager really have to manage the eligibility of recipients of KIP (Smart Indonesia Cards) funds, a procedure that often happens fraudulently and requires a process of calculating the eligibility of receiving aid. ana KIP (Smart Indonesia Card) which is still less accurate makes the manager of the selection of aid recipients have to take into account the eligibility of the beneficiary very well so that the beneficiary is really the right person. A decision support system is used to obtain more precise and accurate results based on the calculation of a hybrid method which is a combination method so that the results obtained are of higher quality, the method used is the ROC-EDAS hybrid method. The results obtained in using this method are found an alternative named isty with the highest score of 0.207622 who became a student who deserved to receive tuition assistance KIP funds